2023
DOI: 10.1002/advs.202205481
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Integration of Atomically‐Thin Indium Tungsten Oxide Transistors for Low‐Power 3D Monolithic Complementary Inverter

Abstract: In this work, the authors demonstrate a novel vertically‐stacked thin film transistor (TFT) architecture for heterogeneously complementary inverter applications, composed of p‐channel polycrystalline silicon (poly‐Si) and n‐channel amorphous indium tungsten oxide (a‐IWO), with a low footprint than planar structure. The a‐IWO TFT with channel thickness of approximately 3‐4 atomic layers exhibits high mobility of 24 cm2 V−1 s−1, near ideally subthreshold swing of 63 mV dec−1, low leakage current below 10−13 A, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Accordingly, HfO 2 -based ferroelectric materials have great potential for use in data-intensive applications such as artificial intelligence, machine learning, edge computing, and in-memory structures. [13][14][15] Despite their high potential, current applications of HfO 2based ferroelectrics in memory devices with M3D integration face limitations due to the high-temperature annealing processes required, typically above 600 °C, which can cause thermal damage to underlying logic or input/output (I/O) circuits. To address this issue, various doping technologies, such as Zr, Al, Si, and Y, have been explored to enable phase transformation at lower temperatures via rapid thermal annealing (RTA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, HfO 2 -based ferroelectric materials have great potential for use in data-intensive applications such as artificial intelligence, machine learning, edge computing, and in-memory structures. [13][14][15] Despite their high potential, current applications of HfO 2based ferroelectrics in memory devices with M3D integration face limitations due to the high-temperature annealing processes required, typically above 600 °C, which can cause thermal damage to underlying logic or input/output (I/O) circuits. To address this issue, various doping technologies, such as Zr, Al, Si, and Y, have been explored to enable phase transformation at lower temperatures via rapid thermal annealing (RTA).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, HfO 2 ‐based ferroelectric materials have great potential for use in data‐intensive applications such as artificial intelligence, machine learning, edge computing, and in‐memory structures. [ 13 , 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, high dopant concentrations of zinc oxide and gallium oxide can suppress the carrier mobility due to the decreased In 2 O 3 fraction in the films. Recent research has explored doping In 2 O 3 films with only several atom % tungsten in the form of tungsten oxides (WO 3 ) to form “IWO” as an alternative semiconducting oxide. , Prior literature suggested that this approach might leverage tungsten’s higher oxygen-bond dissociation energy to enhance threshold voltage stability without significant mobility loss . Reported IWO FETs have demonstrated exceptional on/off ratios, ultrathin channels, and highly scaled gate lengths.…”
mentioning
confidence: 99%
“…Recent research has explored doping In 2 O 3 films with only several atom % tungsten in the form of tungsten oxides (WO 3 ) to form "IWO" as an alternative semiconducting oxide. 15,16 Prior literature suggested that this approach might leverage tungsten's higher oxygen-bond dissociation energy to enhance threshold voltage stability without significant mobility loss. 17 Despite such advancements, the method for depositing the IWO films reported to date is limited to sputtering, a physical deposition technique that involves using energetic species in a plasma struck near a source target or targets to deposit films at relatively low chamber pressures.…”
mentioning
confidence: 99%